The Perspective. A Matter of Points of View (diségno, 2018)
This article presents a study that preceded a lesson for the Department of Architecture of Bologna held to children between eightand fourteen years of age, , as part of an initiative by the University for the dissemination of science. The study presents some experiencesof perspective and stereotomy. Among the objectives of the research is to explain to children, through playing, the illusorypower of perspective and, therefore, the deceptions to which the human perception of space is subjected. For this purpose a smallAmes room was built, studying its decomposition in parts, in a sort of contemporary stereotomy.In the first part of the article, the lesson given to the children is briefly presented, as well as some insights on the theoretical issuesaddressed, which obviously could not be included in the lesson. In the second part, of the study, design and construction of the Amesroom are described.
Keywords: Ames Room; Descriptive Geometry; Mirror; Perception; Stereotomy